Фінансування закладів вищої освіти в Україні та пошук альтернативних джерел - Коваленко, Юлія Михайлівна; Вітренко, Людмила Олексіївна (УДФС України, 2020)
У статті проаналізовано механізм фінансування закладів вищої освіти в Україні. Визначено основні проблеми у фінансуванні вищої освіти. Розглянуто альтернативні джерела фінансування вищої освіти. Охарактеризовано модель освітнього кредитування, яка враховує найкращий світовий досвід та забезпечує доступ до платної вищої освіти різних верств населення. Окреслено перспективи впровадження ендаумент-фондів. Наголошено на необхідності формування освітньо-наукових кластерів із відповідним фінансуванням, що сприятиме активізації освітньо-наукової діяльності.

The article analyzes the mechanism of financing higher education institutions in Ukraine. The main problems in financing higher education have been identified. Alternative sources of funding for higher education are considered. The model of educational crediting is characterized, which takes into account the best world experience and provides access to paid higher education of different segments of the population. Prospects for the introduction of endowment funds are outlined. Emphasis is placed on the need to form educational and scientific clusters with appropriate funding, which will promote the intensification of educational and scientific activities.
Keywords: вища освіта; фінансування; заклади вищої освіти; кредитування; освітньо-наукові кластери; ендаумент-фонди; higher education; financing; higher education institutions; crediting; educational and scientific clusters; endowment funds